2005
DOI: 10.1104/pp.105.064469
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Cell Death in Rice Is Regulated by Ethylene, Gibberellin, and Abscisic Acid

Abstract: Programmed cell death (PCD) of epidermal cells that cover adventitious root primordia in deepwater rice (Oryza sativa) is induced by submergence. Early suicide of epidermal cells may prevent injury to the growing root that emerges under flooding conditions. Induction of PCD is dependent on ethylene signaling and is further promoted by gibberellin (GA). Ethylene and GA act in a synergistic manner, indicating converging signaling pathways. Treatment of plants with GA alone did not promote PCD. Treatment with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
99
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(108 citation statements)
references
References 50 publications
6
99
0
Order By: Relevance
“…A dose-response analysis of ethephon-induced cell death at the third node of wild-type rice cultivar Zhonghua 11 showed that epidermal cell death was induced in a dose-dependent manner by ethephon (see Supplemental Table 1 online) as was shown previously for other rice cultivars (Mergemann and Sauter, 2000;Steffens and Sauter, 2005). Treatment with 15 mM of ethephon resulted in 8.0 and 19.0% cell death after 22 h and 48 h, respectively, as compared with 1.0 and 10.9% in controls.…”
Section: Epidermal Cell Death Is Dependent On the Presence Of Adventimentioning
confidence: 87%
“…A dose-response analysis of ethephon-induced cell death at the third node of wild-type rice cultivar Zhonghua 11 showed that epidermal cell death was induced in a dose-dependent manner by ethephon (see Supplemental Table 1 online) as was shown previously for other rice cultivars (Mergemann and Sauter, 2000;Steffens and Sauter, 2005). Treatment with 15 mM of ethephon resulted in 8.0 and 19.0% cell death after 22 h and 48 h, respectively, as compared with 1.0 and 10.9% in controls.…”
Section: Epidermal Cell Death Is Dependent On the Presence Of Adventimentioning
confidence: 87%
“…The negative effect of ethylene on ABA accumulation in Arabidopsis seedlings was accompanied by lower NCED expression and higher ABA 89-hydroxylase gene expression, as in the signaling cascade described here (Cheng et al, 2009). In rice, ABA treatment hampers flooding-induced AR emergence by preventing epidermal cell death (Steffens and Sauter, 2005), but it has not been reported whether ABA levels actually go down at the site of the preformed AR primordia and whether this is sufficient to mimic the flooding and ethylene responses. ABA also has a prominent role in dormancy initiation and maintenance in seeds and vegetative organ buds (Arend et al, 2009;Nambara et al, 2010;Reddy et al, 2013).…”
Section: Removal Of the Aba Dormancy Signal Activates Ar Primordiamentioning
confidence: 99%
“…Such counteracting role of these hormones relates to their influence on the ROS-scavenging enzymes expression [49]. ABA has been also shown to delay ET-and GA-induced cell death in rice epidermal cells [50]. All these interactions between phytohormones and ROS indicate the complexity of PCD regulation.…”
Section: Hallmarks and The Regulation Of Programmed Cell Deathmentioning
confidence: 99%